Characterization of [11C]Methyl-Losartan as a Novel Radiotracer for PET Imaging of the AT1 Receptor - Antoun, Rawad (Université d'Ottawa / University of Ottawa, 2011)
The Angiotensin II Type 1 (AT1) receptor is the main receptor responsible for the effects of the renin-angiotensin system, and its expression pattern is altered in several diseases. [11C]Methyl-Losartan has been developed based on the clinically used AT1 receptor antagonist Losartan. The aim of this work is to characterize the pharmacokinetics, repeatability and reliability of measurements, binding specificity and selectivity of [11C]Methyl-Losartan in rats using in vivo small animal positron emission tomography (PET) imaging, ex vivo biodistribution and in vitro autoradiography methods. Also, we aim to measure the presence of metabolites in the kidney and plasma using high-performance liquid chromatography. We have demonstrated in vivo that [11C]Methyl-Losartan is taken up in the AT1 receptor-rich kidneys and that it is displaceable by selective AT1 receptor antagonists. Using ex vivo biodistribution, we have confirmed these results and demonstrated that [11C]Methyl-Losartan binds selectively to the AT1 receptor over the AT2, Mas and β-adrenergic receptors. In vitro autoradiography results confirmed these renal binding selectivity studies. [11C]Methyl-Losartan was also shown to have one and two C-11 labeled metabolites in the plasma and kidneys, respectively. In conclusion, [11C]Methyl-Losartan is a promising agent for studying the AT1 receptor in rat models with normal and altered AT1 receptor expression using small animal PET imaging.
Keywords: Renin-angiotensin System; Losartan; [11C]Methyl-Losartan; Renal PET Imaging; Angiotensin II Type 1 (AT1) Receptor